Analisis bahan ajar bahasa arab prespektif al gali dan abdullah - Diah Ana Nur Baiti; Dian Risky Amalia; Muhammad Syihab As’ad (El-Syaker : Samarinda International Journal of Language Studies, 2025)
Arabic textbooks remain the primary reference in the learning process in Madrasahs; however, most of them have not thoroughly considered the socio-cultural, psychological, linguistic, and educational aspects. This gap can hinder the effectiveness of learning and students' understanding of the Arabic language. This study aims to analyze the feasibility of the Arabic textbook for VIII grade Madrasah Tsanawiyah (MTs) based on the perspectives of Abdullah al-Ghali and Abdul Hamid Abdullah, which includes four main aspects of material development. The research adopts a qualitative approach using literature review and content analysis methods. Data were gathered from the Ministry of Religious Affairs' Arabic textbook published in 2020, supported by relevant literature. The results indicate that the textbook performs well in socio-cultural and psychological aspects by integrating Islamic values and organizing content that aligns with students' developmental stages. However, in terms of linguistic and educational aspects, deficiencies were found, such as the absence of a glossary and the limited study guidelines, suggesting the need for further development to support effective and targeted learning.